2007
DOI: 10.1002/cm.20184
|View full text |Cite
|
Sign up to set email alerts
|

The polypeptide composition of moving and stationary neurofilaments in cultured sympathetic neurons

Abstract: Studies on the axonal transport of neurofilament proteins in cultured neurons have shown they move at fast rates, but their overall rate of movement is slow because they spend most of their time not moving. Using correlative light and electron microscopy, we have shown that these proteins move in the form of assembled neurofilament polymers. However, the polypeptide composition of these moving polymers is not known. To address this, we visualized neurofilaments in cultured neonatal mouse sympathetic neurons us… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
36
0

Year Published

2008
2008
2019
2019

Publication Types

Select...
9
1

Relationship

3
7

Authors

Journals

citations
Cited by 44 publications
(37 citation statements)
references
References 55 publications
0
36
0
Order By: Relevance
“…In these studies, intact filaments (1-15 μm of length) represent 95% of the moving structures observed, strongly supporting the polymer model. The transport of NF polymers was recently confirmed by Yan and Brown [326] who showed that NF move in the form of assembled polymers in axons of cultured neonatal mouse sympathetic neurons and, more interestingly, that moving and stationary NF are complex heteropolymers also containing peripherin and α-internexin along >85% of their length [327]. Yuan et al [328] also demonstrated that α-internexin is a key determinant for the axonal transport of NF in CNS.…”
Section: Axonal Transport Of Neurofilamentsmentioning
confidence: 88%
“…In these studies, intact filaments (1-15 μm of length) represent 95% of the moving structures observed, strongly supporting the polymer model. The transport of NF polymers was recently confirmed by Yan and Brown [326] who showed that NF move in the form of assembled polymers in axons of cultured neonatal mouse sympathetic neurons and, more interestingly, that moving and stationary NF are complex heteropolymers also containing peripherin and α-internexin along >85% of their length [327]. Yuan et al [328] also demonstrated that α-internexin is a key determinant for the axonal transport of NF in CNS.…”
Section: Axonal Transport Of Neurofilamentsmentioning
confidence: 88%
“…Neurofilaments are particularly abundant in large myelinated axons [52]. They are obligate heteropolymers that are composed of four subunits: a light (NfL), a medium (NfM) and a heavy (NfH) chain and alpha-internexin [52,53,79]. Elevated levels of CSF neurofilaments have been observed in several neurodegenerative diseases including MS [9,50], amyotrophic lateral sclerosis [8,60] or different subtypes of dementia [7].…”
Section: ■ Myelin Sheath-associated Markersmentioning
confidence: 99%
“…Neurofilaments from the central nervous system (CNS) are heteropolymers that are composed of four subunits, namely neurofilament heavy, medium and light (See poster insert) polypeptides (NFH, NFM and NFL, respectively; also known as NEFH, NEFM and NEFL), as well as a-internexin (Int), whereas in the peripheral nervous system, neurofilaments are made up of NFH, NFM, NFL and peripherin (Beaulieu et al, 1999;Yan et al, 2007;Yuan et al, 2006b). Neurons may also express other intermediate filament proteins, including nestin, synemin, syncoilin and vimentin (Perrin et al, 2005).…”
Section: Neurofilament Structure and Functionmentioning
confidence: 99%